2020
DOI: 10.1371/journal.pone.0241231
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic and molecular survey of the pteridophytes of the Nectandra Cloud Forest Reserve, Costa Rica

Abstract: Floristic surveys are crucial to the conservation of biodiversity, but the vast majority of such surveys are limited to listing species names, and few take into account the evolutionary history of species. Here, we combine classical taxonomic and molecular phylogenetic (DNA barcoding) approaches to catalog the biodiversity of pteridophytes (ferns and lycophytes) of the Nectandra Cloud Forest Reserve, Costa Rica. Surveys were carried out over three field seasons (2008, 2011, and 2013), resulting in 176 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…So far, the nuclear-encoded ribosomal internal transcribed spacer (ITS) region and the chloroplast intergenic spacer trnH-psbA have emerged as candidates for barcoding plants, followed by others including coding sequences from plastid Since a standard plant barcode has been complicated by the trade-off that arises between the high variability of sequences and high conservation of primers, it is then recommended to simultaneously utilize more than one marker as a compromise that best matches the barcoding criteria (Lahaye et al 2008). As a consequence, combinations of multiple barcode markers were shown to improve the ability to classify plants maximally by 60% when compared to a single barcode, which has persuaded researchers out of botany to take the same measures when barcoding other organisms (Group 2009;Li et al 2021;Nitta et al 2020;Zhang et al 2013).…”
Section: Barcodes In Plantsmentioning
confidence: 99%
“…So far, the nuclear-encoded ribosomal internal transcribed spacer (ITS) region and the chloroplast intergenic spacer trnH-psbA have emerged as candidates for barcoding plants, followed by others including coding sequences from plastid Since a standard plant barcode has been complicated by the trade-off that arises between the high variability of sequences and high conservation of primers, it is then recommended to simultaneously utilize more than one marker as a compromise that best matches the barcoding criteria (Lahaye et al 2008). As a consequence, combinations of multiple barcode markers were shown to improve the ability to classify plants maximally by 60% when compared to a single barcode, which has persuaded researchers out of botany to take the same measures when barcoding other organisms (Group 2009;Li et al 2021;Nitta et al 2020;Zhang et al 2013).…”
Section: Barcodes In Plantsmentioning
confidence: 99%
“…Forest monitoring plots, such as the Smithsonian's Forest Global Earth Observatories (ForestGEO) and the National Science Foundation's Long Term Ecological Research (LTER) sites, are rich resources because they have well-verified identifications, vouchered collections, and individually tagged trees that can be revisited by botanists if necessary [43][44][45][46]. Even if no specific monitoring plots have been established, many studies have generated DNA barcode libraries for specific habitats [47], plant communities [48], or regional taxa [49][50][51] and are thereby expanding the global plant genetic library. Individual taxonomists are also generating DNA barcodes for specific groups of plants as either standard markers (e.g., [52][53][54][55]) or as an offshoot of their basic molecular phylogenetic investigations aimed at understanding evolutionary relationships.…”
Section: Building the Plant Dna Barcode Librarymentioning
confidence: 99%
“…The trnL‐F spacer performed well in terms of both amplification success and power to discriminate species in the ferns of Europe (de Groot et al, 2011 ) and vittarioid ferns in East Asia (Chen et al, 2013 ). Recently, Nitta et al ( 2020a ) compared rates of interspecific variation in rbcL in three fern floras (French Polynesia, Costa Rica, and Japan) and found that this marker had a higher identification failure rate in continental areas (Costa Rica and Japan) compared with the isolated islands of French Polynesia, which they attributed to the possibility of higher rates of in situ speciation in continental regions vs. long‐distance dispersal in remote oceanic islands. This highlights the need to consider biogeography in DNA barcoding of fern gametophytes, at least when the provenance of specimens is known.…”
Section: Choosing a Barcode Markermentioning
confidence: 99%